Group V Secreted Phospholipase A2 Induces the Release of Proangiogenic and Antiangiogenic Factors by Human Neutrophils - Loffredo, Stefania; Borriello, Francesco; Iannone, Raffaella; Ferrara, Anne L.; Galdiero, Maria R.; Gigantino, Vincenzo; Esposito, Pasquale; Varricchi, Gilda; Lambeau, Gerard; Cassatella, Marco A.; Granata, Francescopaolo; Marone, Gianni (Frontiers in Immunology, 2017)
Secreted phospholipases A2 (sPLA2s) are extracellular enzymes that catalyze the release of free fatty acids and lysophospholipids from membrane phospholipids and also bind to different receptors (e.g., PLA2R1 or integrins). To date, 12 mammalian sPLA2s have been identified, which play a critical role in pathophysiological processes including inflammation and cancer. sPLA2s activate immune cells such as human neutrophils (PMNs) by enzymatic activity- or receptor-mediated mechanisms. In addition, human PMNs synthesize and store human group V (hGV) and human group X (hGX) sPLA2s in their granules, but only the former is released upon cellular activation. We investigated the effects of sPLA2s on the release of proangiogenic and antiangiogenic factors by PMNs. We found that exogenous hGV and hGX sPLA2s induce the release of vascular endothelial growth factor (VEGF)-A, angiopoietin 1 (Ang1), and CXCL8/IL-8. Only hGV induces the secretion of the antiangiogenic isoform of VEGF-A, namely, VEGF-A165b. While the release of VEGF-A, Ang1, and CXCL8/IL-8 was likely mediated by hGV enzymatic activity and/or binding to PLA2R1 and heparan sulfate proteoglycans, the release of VEGF-A165b requires the interaction with αVβ3 and α4β1 integrins. We also provide evidence that endogenous hGV released by N-formyl-met-leu-phe (fMLF)-activated PMNs is involved in the release of angiogenic factors. The translational relevance of these data is supported by our findings that hGV expression is increased in human samples of lung cancer which are infiltrated by PMNs. Overall, our results suggest that the hGV–neutrophil axis may play a relevant role in the modulation of cancer-related inflammation and angiogenesis.